Współpraca Unii Europejskiej z wybranymi państwami niedemokratycznymi Afryki Subsaharyjskiej w obszarze poszanowania praw człowieka - Kalicka-Mikołajczyk, Adriana (Wydawnictwo Uniwersytetu Wrocławskiego, 2021)
In Art. 3, para. 5, the Treaty on European Union (TEU) lays down the objectives of the Union in relations with the wider world, which are further explained in detail in Art. 21. In the first place, para. 5 refers to the promotion of the Union’s values. The list of values can be found in Art. 2 TEU (“The Union is founded on…”), which lists the principle of democracy, the rule of law and respect for human rights, human dignity, freedom and equality. They are to be upheld and promoted by the Union in the wider world. Thus, they are directly linked to external policy. Next, the list of values in Art. 2 is repeated in Art. 3, para. 5 as objectives of the Union’s external policy and in Art. 21, para. 1 as principles. For this reason, international agreements concluded between the EU and third countries all contain a “human rights clause” as an essential element of the agreement, the violation of which might result in the suspension of the agreement. This article focuses on the human rights clause in relations between the EU and selected non-democratic Sub-Saharan African countries. The main legal basis governing bilateral relations between the EU and those countries is the Cotonou Agreement. The “human rights clause” is to be found in Art. 9 thereof. This clause is especially interesting since it is the only one that has been implemented in practice. Moreover, it is often presented as the most elaborate one, and as a consequence is very often shown as a “model” that should be followed in other international agreements, especially in association agreements. So, the “human rights clause” contained in the Cotonou Agreement has its own characteristic features. Firstly, as it was mentioned above, it is the only one that has been activated in practice. Secondly, the “non-execution clause” is much more detailed, and finally, much more emphasis is laid on political dialogue and on the consultation procedure. This paper provides a propaedeutic analysis of legal cooperation between the EU and selected non-democratic Sub-Saharan countries in the area of human rights protection. Its main objective is to answer the following questions: to what extent the EU cooperates with such countries? What are the issues the clause covers? Is it effective? To what extent could it be enhanced? For analysis, the following countries have been chosen: Chad, Ethiopia, Rwanda, Uganda, and Zimbabwe. According to the Freedom House’s annual Freedom in the World report, the Global Freedom Scores for all these countries do not exceed 35 points, which equates to lack of democracy. Moreover, another feature which all of them have in common is a very low score on the Human Development Index (HDI), which means that all of them belong to the poorest and least developed countries in the world.
Keywords: European Union values; Cotonou Agreement; human rights protection; external policy